Menghidupkan Event Sosial Ramadhan melalui Festival Bulukerto Ber-Ramadhan (FESBUKER) di Kelurahan Bulukerto Magetan - Al Fudiah, Nurul; Aisy, Nurul; Ariqoh, Farihah; Fauziyah, Afifatul; Anriani, Sandra (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2024)
The Bulukerto Ber-Ramadhan Festival (FESBUKER) is one of the efforts to revive Ramadan social activities in Bulukerto Village, Magetan. The main purpose of  this activity is to strengthen the sense of togetherness and solidarity, and strengthen social and religious values in the month of Ramadan. In FESBUKER, several social activities are included, including: competitions for children at the Bulukerto village level, Iftar Together, Bulukerto Storytelling, and Orphan Compensation. The results of this activity show the good participation of the community in FESBUKER activities, as well as strengthening cooperation between village organizations in the implementation of activities. The conclusion of this community service activity is that the Ramadan Festival can be an effective instrument to rally togetherness and strengthen social networks between elements of society. The suggestion for similar activities in the future is to involve more parties from different walks of life to expand their positive impact.